Handbook of Exoplanets 2018
DOI: 10.1007/978-3-319-30648-3_177-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Host Stars using Asteroseismology

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Asteroseismology is one of the most successful methods to precisely infer radii, masses, and ages of exoplanets through the characterization of their host stars (for recent reviews, see Huber 2018;Lundkvist et al 2018). We predicted the asteroseismic yield of known host stars in Cycles 1 and 2 by employing a statistical test (Chaplin et al 2011;Campante et al 2016;Schofield et al 2019) that estimates the detectability of convection-driven, solar-like oscillations in TESS photometry of any given target.…”
Section: Asteroseismologymentioning
confidence: 99%
“…Asteroseismology is one of the most successful methods to precisely infer radii, masses, and ages of exoplanets through the characterization of their host stars (for recent reviews, see Huber 2018;Lundkvist et al 2018). We predicted the asteroseismic yield of known host stars in Cycles 1 and 2 by employing a statistical test (Chaplin et al 2011;Campante et al 2016;Schofield et al 2019) that estimates the detectability of convection-driven, solar-like oscillations in TESS photometry of any given target.…”
Section: Asteroseismologymentioning
confidence: 99%
“…Throughout the course of the NASA Kepler/K2 mission (Borucki et al 2010;Howell et al 2014), asteroseismology has played an important role in the characterization of host stars and their planetary systems (for recent reviews, see Lundkvist et al 2018). Kepler/K2 mainly targeted main-sequence stars, however, preventing a systematic transit survey of red giants and hence robust inference of the planet occurrence around such stars (Huber et al 2013;Lillo-Box et al 2014;Grunblatt et al 2017Grunblatt et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…60), although the determination is obviously affected by other uncertainties in the stellar modelling (Gough 1987). These properties make solar-like oscillations powerful tools for determining the global properties of stars, i.e., mass, radius and age, which are very important for the characterization of exoplanetary systems (for recent reviews, see Christensen-Dalsgaard and Silva Aguirre 2018; Lundkvist et al 2018). Lebreton and Goupil (2014) made a careful analysis of asteroseismic data for a star observed by CoRoT and demonstrated that, combining these with 'classical' observations, precise estimates of the mass and age of the star could be obtained.…”
mentioning
confidence: 99%